Preparation method of trans-structure perovskite solar cell based on mesoporous structure and trans-structure perovskite solar cell
By introducing a mesoporous layer and a self-assembled single-molecular material layer in the preparation process of trans-structured perovskite solar cells, the problems of pinholes and short circuits on the surface of perovskite films are solved, and the photoelectric conversion efficiency and yield of solar cells are improved, which is suitable for large-area production.
Patent Information
- Application Number
- CN202411920164.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-25
AI Technical Summary
During large-scale production of existing trans-structure perovskite solar cells, there are problems such as pinholes, short circuits on the surface of perovskite films and serious dispersion of battery performance.
Using a mesoporous structure-based preparation method, the mesoporous layer and self-assembled single-molecular material layer are prepared on the hole transport layer, so as to improve the wettability of the perovskite solution and the film forming properties of the film, and optimize the interface energy level matching.
It significantly improves the photoelectric conversion efficiency and yield of trans-structured perovskite solar cells, is suitable for large-area production, and maintains the simplicity of the process and the advantages of low annealing temperature.
Smart Images

Figure CN119698210A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a method for preparing a trans-structured perovskite solar cell based on a mesoporous structure, and a perovskite solar cell. Background Art
[0002] In recent years, the development of solar cells based on organic-inorganic hybrid perovskite materials has been very rapid. At present, the highest photoelectric conversion efficiency of a single perovskite solar cell is 26.7%, which is very close to the best performance level of silicon-based solar cells. The structure of perovskite solar cells includes trans structure and formal structure, among which the formal structure can be divided into formal planar structure and formal mesoporous structure. Compared with formal structure perovskite solar cells, inverted structure perovskite solar cells have the advantages of simple preparation process, small hysteresis, low annealing temperature, compatibility with flexible substrates and the ability to build high-efficiency stacked cells. Currently, most inverted structure perovskite cells are planar structures, in which p-interface materials are often made of nickel oxide, self-assembled monolayers and other materials, and n-interface materials are mostly fullerenes and their derivatives (such as C60, PCBM). Experiments have found that whether it is nickel oxide or self-assembled monolayer substrates, the wettability of perovskite solutions on such materials is not very ideal, which may cause pinholes on the surface of the perovskite film, resulting in short circuits, and due to the poor coverage of the perovskite film, the battery performance is seriously dispersed. When the perovskite cell is expanded from a small area to a large area, the problem will become more serious.
[0003] Perovskite solar cells containing mesoporous layers have many advantages. Taking zirconium dioxide mesoporous layers as an example, the introduction of mesoporous zirconium dioxide layers can first greatly improve the wettability of perovskite solution on the substrate, helping to obtain a uniformly covered, pinhole-free perovskite film; secondly, the mesoporous zirconium dioxide layer can prevent direct contact between the back electrode and the bottom charge transfer layer or electrode layer, reducing the possibility of short circuit in the battery; in addition, some conductive mesoporous materials such as TiO2 mesoporous layers, because the mesoporous skeleton layer can be used as a support layer for the perovskite light absorption layer, increase the contact area with the perovskite layer, thereby improving the extraction and transmission efficiency of electrons. At present, the formal structure perovskite solar cells based on TiO2 mesoporous layers have achieved a photoelectric conversion efficiency of 26.5%. However, formal structure perovskite cells have the defects of complex process, large hysteresis, high annealing temperature, and are not suitable for flexible cells and stacked cells. Summary of the invention
[0004] In order to solve the defects of the above-mentioned prior art preparation, the present invention provides a method for preparing an inverse-structured perovskite solar cell based on a mesoporous structure and a perovskite solar cell.
[0005] The present invention adopts the following technical solutions: A method for preparing a trans-structured perovskite solar cell based on a mesoporous structure, comprising the following steps step: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, and preparing a hole transport layer on the transparent conductive oxide substrate by a coating method; the material of the hole transport layer is selected from one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, nickel oxide, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and self-assembled monolayer, and the material preparation method is selected from a solution method; S3: Preparation of mesoporous layer: Select one of Al2O3 slurry and ZrO2 slurry, stir and oscillate with Al2O3 and ZrO2 nanoparticle solution and dispersing solvent to form a solution, wherein the nanoparticle size is set to 5 nm-500 nm, and the solution concentration is set to 0.1 mg mL -1 -20 mg mL -1 , preparing a mesoporous layer on the hole transport layer by a coating method; S4: Preparation of self-assembled monomolecular material layer: select at least one of the self-assembled monomolecular materials 2PACz, MeO-2PACz, Me-4PACz, mix them according to the preset ratio, and select at least one of isopropanol and ethanol as the solvent, with a concentration of 0.1 mg mL -1 -5 mg mL -1 , after uniform mixing, use a coating method to prepare a layer of self-assembled monomolecular material layer on the mesoporous layer; S5: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the self-assembled monomolecular material layer using a coating machine, dropwise adding chlorobenzene anti-solvent during the spin coating, and placing the obtained perovskite light absorbing thin film layer on a hot stage for annealing after the spin coating, wherein the annealing temperature is 100° C. to 300° C., and the annealing time is 5 min to 2 h; S6: Preparation of electron transport layer: The perovskite light absorbing film layer is transferred to an organic material evaporation chamber, and an electron transport layer C60 is evaporated to a thickness of 10-50 nm, followed by a bathocuproin evaporation to a thickness of 2-10 nm at an evaporation rate of 0.1-5 Å s -1 ; S7: Preparation of metal electrode layer: The metal electrode is evaporated in the metal evaporation chamber. The evaporation metal electrode material is selected from gold, silver, and copper. The thickness is 60-200 nm and the evaporation rate is 0.1-10 Å s -1 .
[0006] In some embodiments, in S1, the time intervals for ultrasonic cleaning with deionized water, acetone, glass cleaner, deionized water, and isopropyl alcohol are set to 10-30 min, and the time is the same. The glass is placed in a 60°C forced air drying oven for drying, and the dried transparent conductive glass is treated with ultraviolet ozone for 15 min.
[0007] In some embodiments, in S1, the transparent conductive glass is selected from FTO or ITO conductive glass.
[0008] In some embodiments, in S2, a predetermined self-assembled monomolecular material is selected and added to an ethanol solvent to make the concentration be 0.1-5 mg mL -1 , use a spin coater to evenly apply the solution onto the transparent conductive oxide substrate, the spin coating speed is 1000-10000 rpm, the spin coating time is 10-90 s, and after the spin coating is completed, transfer to a hot plate at 80-150° C. and heat for 5-30 min.
[0009] In some embodiments, in S3, a spin coater is used to evenly coat the preset solution onto the hole transport layer, the spin coating speed is 1000-10000 rpm, the spin coating time is 10-90 s, and after the spin coating is completed, the solution is transferred to a hot plate at 80-300° C. and heated for 5-30 min.
[0010] In some embodiments, in S4, a spin coater is used to evenly coat the preset solution onto the mesoporous layer, the spin coating speed is 1000-10000 rpm, the spin coating time is 10-90 s, and after the spin coating is completed, the solution is transferred to a hot plate at 80-300° C. and heated for 5-30 min.
[0011] In some embodiments, in S5, the perovskite precursor material is selected from lead iodide, lead bromide, iodoformamidine, methylamine bromide, cesium iodide, and rubidium iodide, mixed in a preset ratio, and the solvent is set to a mixed solution of DMF and DMSO, and stirred and shaken in a preset ratio to obtain a perovskite precursor solution Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb(I 0.95 Br 0.05 )3; A proper amount of the perovskite precursor solution is spin-coated onto the self-assembled monomolecular material layer using a spin coater, and the process of adding an anti-solvent during the spin coating includes: First, add an appropriate amount of perovskite precursor solution onto the self-assembled monomolecular material layer, and then turn on the spin coater for spin coating. The first step is to select a rotation speed range of 300-1000 rpm, and the speed increase rate is 200 rpm s -1 , time 10s; Step 2: Select the speed range of 2000-8000 rpm, and the speed increase rate is 2000 rpm s -1 The total spin coating time range of the first step and the second step is set to 30-90s, and 150 μL of anti-solvent chlorobenzene is added 10 s before the end of spin coating, and the amount of anti-solvent is 100 microliters to 5 milliliters.
[0012] In some embodiments, in S6, the perovskite light absorbing thin film layer is transferred to an organic material evaporation chamber, an electron transport layer C60 is evaporated to a thickness of 30 nm, and then a bathocuproin is evaporated to a thickness of 7 nm at an evaporation rate of 0.3 Å s -1 .
[0013] In some embodiments, in S7, a metal electrode is evaporated in a metal evaporation chamber, and the evaporated metal electrode material is selected from silver, with a thickness of 100 nm and an evaporation rate of 0.1-10 Å s -1 The rate was adjusted by stepwise rate control. When the thickness of the evaporated metal was 0-10 nm, the rate was 0.1 Å s -1 ; When the thickness is 10-20 nm, the rate is 0.2 Å s -1 ; When the thickness is 20-30 nm, the rate is 0.3 Å s -1 ; When the thickness is 30-40 nm, the rate is 0.3 Å s -1 ; When the thickness is 40-50 nm, the rate is 0.4 Å s -1 ; When the thickness is 50-60 nm, the rate is 0.5 Å s -1 ; When the thickness is 60-70 nm, the rate is 0.6 Å s -1 ; When the thickness is 70-100 nm, the rate is 1-10 Å s -1 .
[0014] The present invention also includes an inverted perovskite solar cell, which is prepared using the above-mentioned method for preparing an inverted perovskite solar cell based on a mesoporous structure. Beneficial Effects
[0015] The present invention discloses a preparation method of an inverse structure perovskite solar cell based on a mesoporous structure, a perovskite film and an inverse structure perovskite solar cell. Compared with the prior art, the present invention has the following advantages: The present invention discloses a method for preparing a high-performance inverse-structure perovskite solar cell based on a mesoporous structure. The method comprises preparing a mesoporous layer on a hole transport layer, and then preparing a self-assembled monolayer on the mesoporous layer, thereby comprehensively utilizing the advantages of the mesoporous layer and the self-assembled monolayer, improving the wettability of the perovskite solution on a substrate, greatly improving the film-forming property of the perovskite film, obtaining good interface energy level matching, increasing the extraction rate of photogenerated carriers, and reducing non-radiative recombination losses at the interface, thereby obtaining an inverse-structure perovskite solar cell with high efficiency, stability, high yield rate, and suitability for large-scale production. Meanwhile, the inverse-structure perovskite solar cell has the advantages of simple preparation process, low hysteresis, low annealing temperature, compatibility with flexible substrates, and the ability to construct high-efficiency stacked cells. Experiments have found that the photoelectric conversion efficiency of the inverse-structure perovskite solar cell obtained based on the process of the present invention is 25.12%, and the yield rate reaches 98%, while the photoelectric conversion efficiency of the inverse-structure perovskite solar cell in the prior art is 23.51%, and the yield rate is only 60%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments, which constitute a part of the present invention. The schematic embodiments of the present invention and their descriptions explain the present invention and do not constitute improper limitations on the present invention. In the drawings: Figure 1 A flow chart of a method for preparing a trans-structured perovskite solar cell based on a mesoporous structure provided by an embodiment of the present invention; Figure 2 A schematic diagram of a structure formed during the preparation of a mesoporous inverse-structure perovskite solar cell provided in an embodiment of the present invention; Figure 3 JV curve diagram of the inverted structure perovskite solar cell provided for the embodiment of the invention. DETAILED DESCRIPTION
[0017] The following is a description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, including various details of the embodiments of the present invention to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Similarly, for clarity and conciseness, the description of well-known functions and structures is omitted in the following description.
[0018] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they cannot be understood as limitations on the present invention.
[0019] like Figure 1 - Figure 3 As shown, the technical solution of the present invention: A method for preparing a trans-structured perovskite solar cell based on a mesoporous structure comprises the following steps: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, and preparing a hole transport layer on the transparent conductive oxide substrate by a coating method; the material of the hole transport layer is selected from one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, nickel oxide, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and self-assembled monolayer, and the material preparation method is selected from a solution method; S3: Preparation of mesoporous layer: Select one of Al2O3 slurry and ZrO2 slurry, stir and oscillate with Al2O3 and ZrO2 nanoparticle solution and dispersing solvent to form a solution, wherein the nanoparticle size is set to 5 nm-500 nm, and the solution concentration is set to 0.1 mg mL -1 -20 mg mL -1 , preparing a mesoporous layer on the hole transport layer by a coating method; S4: Preparation of self-assembled monomolecular material layer: select at least one of the self-assembled monomolecular materials 2PACz, MeO-2PACz, Me-4PACz, mix them according to the preset ratio, and select at least one of isopropanol and ethanol as the solvent, with a concentration of 0.1 mg mL -1 - 5 mg mL -1 , after uniform mixing, use a coating method to prepare a layer of self-assembled monomolecular material layer on the mesoporous layer; S5: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the self-assembled monomolecular material layer using a coating machine, dropwise adding chlorobenzene anti-solvent during the spin coating, and placing the obtained perovskite light absorbing thin film layer on a hot stage for annealing after the spin coating, wherein the annealing temperature is 100° C. to 300° C., and the annealing time is 5 min to 2 h; S6: Preparation of electron transport layer: The perovskite light absorbing film layer is transferred to an organic material evaporation chamber, and an electron transport layer C60 is evaporated to a thickness of 10-50 nm, followed by a bathocuproin evaporation to a thickness of 2-10 nm at an evaporation rate of 0.1-5 Å s -1 ; S7: Preparation of metal electrode layer: The metal electrode is evaporated in the metal evaporation chamber. The evaporation metal electrode material is selected from gold, silver, and copper. The thickness is 60-200 nm and the evaporation rate is 0.1-10 Å s -1 .
[0020] The preferred embodiments disclosed in the present invention are as follows: Figure 1-Figure 3 As shown: The present invention discloses a method for preparing a trans-structured perovskite solar cell based on a mesoporous structure, comprising the following steps: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is ultrasonically cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol in sequence. The transparent conductive glass is usually selected from FTO or ITO conductive glass. In this embodiment, FTO transparent conductive glass is selected. The ultrasonic cleaning time is set to 10-30 min. In this embodiment, the ultrasonic cleaning time is set to 10 min. Then, it is placed in a 60°C forced air drying oven for drying. The dried transparent conductive glass is treated with ultraviolet ozone for 15 min to obtain a transparent conductive oxide substrate.
[0021] S2: Preparation of hole transport layer: The FTO transparent conductive oxide substrate is placed in a glove box with a nitrogen atmosphere, wherein the water and oxygen content in the glove box is less than 0.01 ppm, and a hole transport layer is prepared on the transparent conductive oxide substrate, wherein the material of the hole transport layer is selected from one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, nickel oxide, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and a self-assembled monolayer, and the material preparation method includes a solution method, a sol-gel method, a magnetron sputtering method, an atomic layer deposition method, and a combustion method, and the present invention selects a solution method; Select a self-assembled monolayer with MeO-2PACz as the material and add ethanol solvent to make the concentration 0.1-5 mg mL -1 , the concentration in this example is 0.3 mg mL-1 ; A spin coater, a slit coater, a doctor blade coater and an inkjet printer can be used. In this embodiment, a LEBO spin coater is selected. The spin coating speed is 1000-10000 rpm, which is set to 3000 rpm in this embodiment. The spin coating time is 10-90s, which is set to 30 s in this embodiment. After the spin coating is completed, it is transferred to a 100°C hot stage for heating for 10 min; In this embodiment, the spin coating speed is selected to be 3000 rpm, the spin coating time is 30 s, and after the spin coating is completed, it is transferred to a 80-150°C hot stage for heating for 5-30 min. In this embodiment, a 100°C hot stage is selected for heating for 10 min.
[0022] S3: Preparation of mesoporous layer: One of Al2O3 slurry and ZrO2 slurry is selected. In this embodiment, Al2O3 slurry is selected, and the Al2O3 and ZrO2 nanoparticle solution and the dispersion solvent are stirred and shaken to form a solution, wherein the nanoparticle size is set to 5 nm-500 nm, and the solution concentration is set to 0.1 mg mL -1 -20 mg mL -1 In this example, the nanoparticle size is 50 nm, the dispersion solvent is ethanol, and the solution concentration is 10 mg mL -1 , use a spin coater to evenly apply the preset solution to the hole transport layer, the spin coating speed is 1000-10000 rpm, the spin coating speed in this embodiment is 3000 rpm, the spin coating time is 10-90 s, the spin coating time is taken as 30 s, after the spin coating is completed, transfer to 80-300°C hot stage and heat for 5-30 min, and in this embodiment, a 100°C hot stage is selected to heat for 10 min.
[0023] S4: Preparation of self-assembled monolayers: At least one of the self-assembled monomolecular materials 2PACz, MeO-2PACz, and Me-4PACz was selected and mixed according to a preset ratio. The solvent was at least one of isopropanol and ethanol, and the concentration was 0.1 mg mL -1 Up to 5 mg mL -1 In this example, the self-assembled monomolecular material selected was MeO-2PACz, with a concentration of 0.3 mg mL -1 , the solvent is ethanol, after mixing evenly, use a spin coater to evenly apply the preset solution to the mesoporous layer, the spin coating speed is 1000-10000 rpm, the spin coating time is 10-90 s, in this embodiment, the spin coating speed is 3000 rpm, the spin coating time is 30 s, after the spin coating is completed, transfer to 80-300°C hot stage for heating for 5-30 min, in this embodiment, a 100°C hot stage is selected for heating for 10 min.
[0024] S5: Preparation of perovskite light absorbing thin film layer: Adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; The perovskite precursor materials are selected from lead iodide (PbI2), lead bromide (PbBr2), iodomethane (FAI), methylamine bromide (MABr), cesium iodide (CsI), and rubidium iodide (RbI), and are mixed according to a preset ratio. For example, 1 mL of perovskite solution is prepared, and 19.5 mg CsI, 15.9 mg RbI, 8.4 mgMABr, 219.5 mg FAI, 656.9 mg PbI2, and 27.5 mg PbBr2 are added. The concentration is 1.5 M, and the solvent is set to a mixed solution of DMF and DMSO, DMF:DMSO=4:1. Stir and shake to obtain a perovskite precursor solution Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb(I 0.95 Br 0.05 )3.
[0025] A proper amount of the perovskite precursor solution is spin-coated onto the self-assembled monomolecular material layer using a coating machine, and chlorobenzene anti-solvent is added dropwise during the spin coating. The process includes: First, add an appropriate amount of perovskite precursor solution onto the self-assembled monomolecular material layer, and then turn on the spin coater for spin coating: Step 1: Select the speed range of 300-1000 rpm, and the speed increase rate is 200 rpm s -1 , time 10s, the speed selected in this embodiment is 1000 rpm; Step 2: Select the speed range of 2000-8000 rpm, and the speed increase rate is 2000rpm s -1 In this embodiment, the rotation speed is 5000 rpm; the total spin coating time range of the first step and the second step is set to 30-90s, and the total spin coating time is 35s in this embodiment; the amount of anti-solvent is 100 microliters to 5 milliliters, and 150 μL of anti-solvent chlorobenzene is added 10 s before the end of spin coating, and the film is placed on a hot stage with a temperature of 100°C to 300°C, and the annealing time is 5 min to 2 h. In this embodiment, the film is placed on a hot stage with a temperature of 100°C and the annealing time is 30 min.
[0026] S6: Preparation of electron transport layer: The perovskite light absorbing film layer is transferred to an organic material evaporation chamber, and an electron transport layer C60 is evaporated to a thickness of 10-50 nm, and a thickness of 30 nm is selected in this embodiment, and then bathocuproin (BCP) is evaporated to a thickness of 2-10 nm, and a thickness of 7 nm is selected in this embodiment, and the evaporation rate is 0.1-5 Å s -1 , the evaporation rate is 0.3 Å s -1 .
[0027] S7: Preparation of metal electrode layer: The metal electrode is evaporated in the metal evaporation chamber. The evaporation metal electrode material is selected from gold, silver, and copper. The thickness is 60-200 nm and the evaporation rate is 0.1-10 Å s -1 In this embodiment, silver is selected as the evaporated metal electrode material with a thickness of 100 nm. Step-by-step rate control is adopted. When the thickness of the evaporated metal is 0-10 nm, the rate is 0.1 Å s -1 ; When the thickness is 10-20 nm, the rate is 0.2 Å s -1 ; When the thickness is 20-30 nm, the rate is 0.3 Å s -1 ; When the thickness is 30-40 nm, the rate is 0.3 Å s -1 ; When the thickness is 40-50 nm, the rate is 0.4 Å s -1 ; When the thickness is 50-60 nm, the rate is 0.5 Å s -1 ; When the thickness is 60-70 nm, the rate is 0.6 Å s -1 ; When the thickness is 70-100 nm, the rate is 1-10 Å s -1 ,like Figure 1 , Figure 2 shown.
[0028] The inverse-structured perovskite solar cell is prepared using a preparation method of an inverse-structured perovskite solar cell based on a mesoporous structure.
[0029] The experiment found that the photoelectric conversion efficiency of the inverted perovskite solar cell obtained by the process of the present invention was 25.12%, and the yield rate reached 98%. Figure 3 As shown; Figure 3 : This is a JV curve diagram of the inverted perovskite solar cell according to an embodiment of the present invention; while the photoelectric conversion efficiency of the inverted perovskite solar cell in the prior art is 23.51%, and the yield rate is only 60%.
[0030] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing a trans-structured perovskite solar cell based on a mesoporous structure, characterized in that: The steps include: S1: Preparation of transparent conductive oxide substrate: The etched transparent conductive glass is cleaned with deionized water, acetone, glass cleaning agent, deionized water, and isopropyl alcohol ultrasonically in sequence; dried in a blast drying oven; the dried transparent conductive glass is treated with ultraviolet ozone to obtain a transparent conductive oxide substrate; S2: Preparation of hole transport layer: placing the transparent conductive oxide substrate in a glove box with a nitrogen atmosphere, and preparing a hole transport layer on the transparent conductive oxide substrate by a coating method; the material of the hole transport layer is selected from one of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, nickel oxide, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], and self-assembled monolayer, and the material preparation method is selected from a solution method; S3: Preparation of mesoporous layer: Select one of Al2O3 slurry and ZrO2 slurry, stir and oscillate with Al2O3 and ZrO2 nanoparticle solution and dispersing solvent to form a solution, wherein the nanoparticle size is set to 5 nm-500 nm, and the solution concentration is set to 0.1 mg mL -1 -20 mg mL -1 , preparing a mesoporous layer on the hole transport layer by a coating method; S4: Preparation of self-assembled monomolecular material layer: select at least one of the self-assembled monomolecular materials 2PACz, MeO-2PACz, and Me-4PACz, mix them according to a preset ratio, and select at least one of isopropanol and ethanol as the solvent, with a concentration of 0.1 mg mL -1 - 5 mg mL -1 , after uniform mixing, use a coating method to prepare a layer of self-assembled monomolecular material layer on the mesoporous layer; S5: Preparation of a perovskite light absorbing thin film layer: adding a perovskite precursor material to a corresponding solvent in a preset proportion, stirring and oscillating, to obtain a perovskite precursor solution; Spin coating the perovskite precursor solution onto the self-assembled monomolecular material layer using a multi-step continuous spin coating method using a spin coater, dropwise adding chlorobenzene anti-solvent during the spin coating, and placing the obtained perovskite light absorbing thin film layer on a hot stage for annealing after the spin coating, wherein the annealing temperature is 100° C. to 300° C., and the annealing time is 5 min to 2 h; S6: Preparation of electron transport layer: The perovskite light absorption film layer is transferred to an organic material evaporation chamber, and an electron transport layer C60 is evaporated to a thickness of 10-50 nm, followed by evaporation of bathocuproin to a thickness of 2-10 nm at an evaporation rate of 0.1-5 Å s -1 ; S7: Preparation of metal electrode layer: Evaporation of metal electrode in a metal evaporation chamber. The evaporation metal electrode material is selected from one of gold, silver and copper. The thickness is 60-200 nm and the evaporation rate is 0.1-10 Å s -1 .
2. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S1, the time intervals for ultrasonic cleaning with deionized water, acetone, glass cleaning agent, deionized water, and isopropanol are set to 10-30 min respectively, and the time is the same. The glass is placed in a 60°C forced air drying oven for drying, and the dried transparent conductive glass is treated with ultraviolet ozone for 15 min.
3. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S1, the transparent conductive glass is selected from FTO or ITO conductive glass.
4. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S2, select the preset self-assembled monomolecular material and add ethanol solvent to make the concentration 0.1-5 mg mL -1 , use a spin coater to evenly apply the solution onto the transparent conductive oxide substrate, the spin coating speed is 1000-10000 rpm, the spin coating time is 10-90 s, and after the spin coating is completed, it is transferred to a hot stage at 80-150° C. and heated for 5-30 min.
5. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S3, a spin coater is used to evenly apply the preset solution onto the hole transport layer. The spin coating speed is 1000-10000 rpm, and the spin coating time is 10-90 s. After the spin coating is completed, the solution is transferred to a hot plate at 80-300° C. and heated for 5-30 min.
6. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S4, a spin coater is used to evenly coat the preset solution onto the mesoporous layer. The spin coating speed is 1000-10000 rpm and the spin coating time is 10-90 s. After the spin coating is completed, the solution is transferred to a hot plate at 80-300° C. and heated for 5-30 min.
7. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S5, the perovskite precursor material is selected from lead iodide, lead bromide, iodoformamidine, methylamine bromide, cesium iodide, and rubidium iodide, which are mixed in a preset ratio, and the solvent is set to a mixed solution of DMF and DMSO, which is stirred and shaken in a preset ratio to obtain a perovskite precursor solution Rb 0.05 Cs 0.05 MA 0.05 FA 0.85 Pb(I 0.95 Br 0.05 )3; A proper amount of the perovskite precursor solution is spin-coated onto the self-assembled monomolecular material layer using a spin coater, and the process of adding an anti-solvent during the spin coating includes: First, add an appropriate amount of perovskite precursor solution onto the self-assembled monomolecular material layer, and then turn on the spin coater for spin coating. The first step is to select a rotation speed range of 300-1000 rpm, and the speed increase rate is 200 rpm s -1 , time 10s; Step 2: Select the speed range of 2000-8000 rpm, and the speed increase rate is 2000 rpm s -1 The total spin coating time range of the first step and the second step is set to 30-90s, and 150 μL of anti-solvent chlorobenzene is added 10 s before the end of spin coating, and the amount of anti-solvent is 100 microliters to 5 milliliters.
8. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S6, the perovskite light absorbing film layer is transferred to an organic material evaporation chamber, and an electron transport layer C60 is evaporated to a thickness of 30 nm, and then bathocuproin is evaporated to a thickness of 7 nm at an evaporation rate of 0.3 Å s -1 .
9. The method for preparing a mesoporous inverse perovskite solar cell according to claim 1, characterized in that: In S7, The metal electrode is evaporated in the metal evaporation chamber. The evaporation metal electrode material is silver with a thickness of 100 nm and an evaporation rate of 0.1-10 Å s -1 The rate is 0.1 Å s when the thickness of the evaporated metal is 0-10 nm. -1 ; When the thickness is 10-20 nm, the rate is 0.2 Å s -1 ; When the thickness is 20-30 nm, the rate is 0.3 Å s -1 ; When the thickness is 30-40 nm, the rate is 0.3 Å s -1 ; When the thickness is 40-50 nm, the rate is 0.4 Å s -1 ; When the thickness is 50-60 nm, the rate is 0.5 Å s -1 ; When the thickness is 60-70 nm, the rate is 0.6 Å s -1 ; When the thickness is 70-100 nm, the rate is 1-10 Å s -1 .
10. An inverted perovskite solar cell, characterized in that: It is prepared using the method for preparing a mesoporous structure-based inverse perovskite solar cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Reverse mesoporous perovskite solar cell structure and preparation method thereof
CN111525033A
Trans-perovskite solar cell, preparation method thereof and electric equipment
CN116782680A
Hole transport layer prepared from mesoporous nickel oxide and self-assembly material, perovskite solar cell formed by hole transport layer and preparation method of perovskite solar cell
CN117241640A
Trans-perovskite solar cell preparation method and solar cell
CN118201376A
Solar cell and preparation method thereof, photovoltaic module and photovoltaic system
CN118414002A